2016
DOI: 10.21125/edulearn.2016.1836
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptance and Use of the E-Learning Systems Among the University Teachers in Ecuador

Abstract: The success of an e-learning system depends largely on the acceptance and use that teachers give this tool. After critically evaluate models of technology adoption, including the Technology Acceptance Model (TAM) and TAM2, we built a conceptual model to predict the level of acceptance and use of elearning system among teachers. This model extends TAM2 and includes technical support, computer self-efficacy, social influence, perceived enjoyment and satisfaction. Data were collected from 145 teachers of a Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
2
13
0
1
Order By: Relevance
“…In the TAM, TAM2 and DTPB, PEU was theorized as a direct determinant of BI. In addition, a number of researchers found a support to the indirect relationship of PEU on BI through PU (Yousafzai et al, 2007a;Al-Tomny et al, 2016;Ramirez-Anormaliza et al, 2016;. Strong evidence supported the important role that PEU play in predicting the BI (Davis, 1989;Igbaria et al, 1997;Tarhini, Hone, & Liu, 2014a;Abdullah & Ward, 2016;.…”
Section: Perceived Ease Of Usementioning
confidence: 95%
“…In the TAM, TAM2 and DTPB, PEU was theorized as a direct determinant of BI. In addition, a number of researchers found a support to the indirect relationship of PEU on BI through PU (Yousafzai et al, 2007a;Al-Tomny et al, 2016;Ramirez-Anormaliza et al, 2016;. Strong evidence supported the important role that PEU play in predicting the BI (Davis, 1989;Igbaria et al, 1997;Tarhini, Hone, & Liu, 2014a;Abdullah & Ward, 2016;.…”
Section: Perceived Ease Of Usementioning
confidence: 95%
“…As TAM is quantitative in nature, the decision was made to use online survey for data collection [21]. Althobaiti and Mayhew asserted that surveys are suitable for the evaluation of LMS [37].…”
Section: A Data Collectionmentioning
confidence: 99%
“…Abdullah and Ward in [18] conducted a quantitative meta-analysis of 107 studies in e-learning adoption and concluded that 17 out of 27 (63%) studies found a positive influence between CSE and PU and 33 out of 41 (80%) studies found a positive influence between CSE and PEOU. In the studies [21]- [23] of developing countries (as the case of Saudi Arabia), it was found that CSE influences PEOU of e-learning and does not affect PU. It was found that CSE of Jordanian students is correlated with PEOU [24].…”
Section: A Computer Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations